ANALISIS KEMAMPUAN MENULIS PANTUNSISWAKELASVSD AN NAMIROH PUSATKECAMATAN TAMPAN KOTA PEKANBARU - Nora Afrilia Afrilia; Hamizi '; Gustimal witri witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : In era globalization era, poem is not interested by students when learning Indonesian language at the class. it is because of many things with modern technology which is make students ignore to understanding poem , performance of poem and practice to write poem. Consequently researcher conducted this research toward fifth grade students of SD An Namiroh pusat pekanbaru to describe of students’ writing ability about poem. The population of research is all of fifth grade students SD An Namiroh Pekanbaru. The sample of this research was 140 students of fifth grade of SD An Namiroh Pekanbaru. The research has given essay test to measure their writing ability. Score of determining is with conversion score formula.Analysis of writing ability with average score formula. Poem analyzed based on four aspects. They are the number of lines in the stanza, the number of syllables each lines, poetry and content. Based on result of data analysis, students’ writing ability about poem which less category, there are 35 students or 25% of sample, the average category , there are 20 students or 20 or 14,3 %of sample, the good category is 21 students or 15% of sample, the excellent category is 64 students or 45,7% of sample. Therefore, based on the data above, in conclusion students’ writing ability of poem at Fifth grade of SD An namiroh pekanbaru is 78 score or average category. Key Word : Writing ability , Poem